Morte no corpo, vida no espírito: o processo de luto na prática espírita da psicografia - Guarnieri, Maria Cristina Mariante (2001)
The tendency to deal with death and dying as commonplace facts has grown a lot. The secularized world has brought great progress to the humanity. However, a hard reality is revealed: there is no place to expressions such as suffering, pain and death. This reality is already perceptible in the big cities, where the rites and spaces that can integrate and arise reflections on death are of little value. Not only does the contact with death oblige us to find another meaning in life, but it also makes us seek for the one of the death. Starting with the comprehension of death and mourning in the human development, based on authors such as Carl Gustav Jung, John Bowlby and Colin Parkes, it has been possible to realize that some ampliation was needed. Peter Berger and Thomas Luckmann s sociology of the knowledge, Edgar Morin s death anthropology and the historian Philipe Aries contributions helped to build a more complete vision of that human being towards his mortality consciousness. This dissertation s objective is to demonstrate the importance of the religious space, specifically the spiritism, to keep in the contents of mourning elaboration and questions about being finite as human beings. In spiritism and its belief in life after death, it is understood that it is possible to communicate with the spirits of the dead. The practice of psychography, analized in this work, ends up making this elaboration easier and creating a warm environment for the mourner and his questions. To finish, 17 mourners talking about their loss experience were heard, supporting the importance of opening ourselves to the question of the sense of being human. This work intends to contribute to the religiosity comprehension as part of the human psychism. The individual existence is full of beliefs, symbols and religious attitudes that allow to integrate death in its history, mainly to rescue and value life